Imej wanita dalam novel “Asam Pedas untuk Dia” dan “Ombak Rindu”: Kajian kritik feminis / Sarojini Karuppiah - Sarojini , Karuppiah (2018)
This study uses a novel genre as resources of the study to study the position or ranks of women in literature of men author or women author who writes in the men marking system. Women author normally will higher the rank of women and will also dive in the women’s feeling in an effort of producing their masterpiece. But an author regardless woman or man that sees a woman with a man’s view will put the image and emotions of women into collision in their masterpiece. This study is done to recognize the details of women’s stereotypes that exist in the ‘Asam Pedas untuk Dia’novel by Nureen Mirza and ‘Ombak Rindu’ by Fauziah Ashari. Two women author has produced this novel, but in a marking system as a man. These two novels have been chosen as a study material because these two novels has gotten a great response among readers. This is proven by the production of drama and film as an adaptation from the novel for public viewing. This material of study has been used to trigger studies based on feminism theory that uses the approach of Feminist Critics by Elaine Showalter.Elaine Showalter has introduced another approach that studies the work of women about women, but the researcher has used Feminist Critics to study both novels as a medium to measure the accuracy of the objective of the study. This is because, the author has seen women from the men’s perspective. This fact is proven from the stereotype details contained in the ‘Asam Pedas untuk Dia’ and ‘Ombak Rindu’ novels.